Antifungal and functional properties of starch-gellan films containing thyme (Thymus zygis) essential oil. (October 2018) - Sapper, Mayra; Wilcaso, Paola; Santamarina, M. Pilar; Roselló, Josefa; Chiralt, Amparo
Abstract: Films based on starch-gellan blends at 9:1 and 8:2 ratios containing emulsified or lecithin encapsulated thyme ( Thymus zygis ) essential oil (EO) (0.25 or 0.5 g/g polymer), were obtained by casting method and characterized as to their structural, functional (mechanical, barrier and optical) and in vitro antifungal properties against Alternaria alternata (AA) and Botryotinia fuckeliana (BF). The EO retention during the film formation was also quantified. Lecithin encapsulation of the EO allowed for greater oil retention (45–55%), which enhanced the antifungal activity of the films, which were more effective against BF than AA. All films exhibited high oxygen barrier capacity, while lecithin improved the films water barrier properties and gloss, conferring them with a slightly brownish color. Lecithin also reduced the film stiffness and resistance to break and extensibility. Of the studied formulations, 8:2 S:G films with lecithin-encapsulated EO were very effective at controlling fungal growth, while exhibiting adequate functional properties as packaging/coating materials. Highlights: Starch-gellan films showed antifungal activity dependent on the essential oil content. Free or lecithin encapsulated oil changed the film structure and functionality. Lecithin encapsulation greatly improved the essential oil retention in the films. Botryotinia fuckeliana was more sensitive than Alternaria alternata to the active films.